PEDAGOGICAL TRANSLATION IN SECOND LANGUAGE ACQUISITION - Sindy Alicia Gunawan (Universitas Putera Batam, 2020)
As the pioneering pedagogical instrument in Second Language Acquisition (SLA), translation has been securing its place in the academic discourse about SLA. However, confusion over the definition of pedagogical translation has been brought by the rise of translation studies. Besides, the attitude of SLA scholars toward the use of translation in language classroom has evidently changed overtime. This article seeks to reassess the theoretical position of translation in SLA and in translation studies, as well as to examine the current practice of pedagogical translation in SLA classroom. Based on the analysis results, translation is theoretically divided into pedagogical translation (translation as a means) and real translation (translation as an end). Both are regarded as different and independent activities, but they are connected and related at some levels in the practice. As for the current practice of pedagogical translation in SLA, it is found that the recent trend for pedagogical translation is integration with other method such as audiovisual and technology which shows that translation is still relevant to today’s SLA context that it continues being innovated.